Investor demand, market efficiency and spot-futures relation: Further evidence from crude palm oil - Go, Y.H.; Lau, W.Y. (Elsevier, 2017)
This study examines the hypothesis of Tilton et al. (2011) that assert investor demand affects commodity prices when spot and futures prices are closely correlated during strong contango in a hard commodity like copper. However, using daily data of crude palm oil (CPO) spot and futures prices from January 2000 to July 2016, after taking into account the variance of the increments in a random walk as measured by variance ratio, our study finds that spot and futures prices are highly correlated during backwardation period. It is further observed that: First, investor demand on the futures market is highly correlated with spot and futures prices during backwardation, but lesser during weak contango, and the least correlated during strong contango. Second, the efficiency of the futures market is related to the degree of correlation between spot and futures price changes. High efficient information transmission in the futures market is linked to a high correlation between spot and futures markets and vice versa. Therefore, we extend the hypothesis that the preference of holding a long position in the futures market is due to the anticipation of insufficient supply of CPO which happens during the backwardation period.